Karakteristik Kopi Robusta Argopuro dengan Metode Pengolahan Honey Process dan Penambahan Nanas - Mas Anang Fuad Rifa’i; Winda Amilia; Miftahul Choiron; Andrew Setiawan Rusdianto; Nidya Shara Mahardika (JOFE : Journal of Food Engineering, 2023)
This study aims to determine the physical quality characteristics and the effect of adding pineapple concentration on the hedonic test of the Robusta Argopuro coffee method honey process. The research method used a completely randomized design with a single factor in 3 treatments using pineapple pulp concentrations (30%, 50%, and 80%) with 3 replications. The results of the study did not find live insects and the appearance of a moldy or rotting odor in the coffee greenbean with a defect value of 9.5 is included in the quality category 1. The seed size test results in a large seed size classification. The water content test produced the highest value of 9.97 at 80% concentration and the lowest 9.33 at 0% concentration and the hedonic test of aroma, color, sweetness, acidity, fruity, bitter, body, aftertaste, balance, and, overall produced the highest values in a row, namely 3.46 at a concentration of 0%; 3.56 at 50% concentration; 3.09 at 80% concentration; 3.22 at 80% concentration. 3.06 at 80% concentration; 3.24 at 50% concentration; 3.20 at 80% concentration; 3.38 at 30% concentration, 3.34 at 80% concentration; and 3.47 at 80% concentration. On the results of the physical quality test of coffee greenbean complies with SNI 01-2907-2008 standard. %. Argopuro robusta coffee brew honey process with the addition of pineapple pulp at a concentration of 80% produced the highest hedonic value.